Creatine supplementation and cognitive function across different populations: A narrative review - Kalinowska, Zuzanna; Aleksandrowicz, Hanna; Krężel, Maciej; Krężel, Olga; Rybińska, Marcelina; Szafraniec, Artur (Journal of Education, Health and Sport, 2026)
Creatine is a naturally occurring compound in the body that plays a key role in cellular energy metabolism by participating in the renewal of adenosine triphosphate (ATP). Due to the importance of ATP for neuronal function, creatine supplementation has been the subject of research into its potential effects on cognitive function. The aim of this study was to analyze the available scientific data on the effects of oral creatine supplementation on overall cognitive performance, memory and attention in various populations. Based on a review of selected studies, it was found that creatine supplementation might have a moderate, context-dependent effect on cognitive function. The most consistent results were observed in the elderly, especially in terms of memory. Beneficial effects were also noted in conditions of increased energy demand, such as sleep deprivation. In the population of young, healthy adults, the results remain inconclusive. In turn, in clinical studies on neurodegenerative diseases, despite promising theoretical foundations, no significant clinical benefits have been demonstrated. The available data suggest that the effect of creatine on cognitive function may be most pronounced in situations of reduced energy availability. Further high-quality, objective clinical studies are needed to determine the optimal doses, supplementation duration, and potential therapeutic indications.